Armed Spiders Phoneutria Perty (Arachnida: Araneae: Ctenidae) - Lawrence E. Reeves; Jennifer Lynn Gillett-Kaufman (EDIS)
Phoneutria are nocturnal hunters that actively forage and overcome prey with potent venom rather than relying on a web for prey capture. Members of the genus are among the most medically important spiders in the world (Vetter and Isbister 2008). https://edis.ifas.ufl.edu/in1207